2022
DOI: 10.1177/19476035221141419
|View full text |Cite
|
Sign up to set email alerts
|

The Cartilage Protective Effect of Labrum Reconstruction Using Meniscus Allograft Compared with Labrum Resection in a Porcine Model

Abstract: Purpose This study aimed to verify the femoral head cartilage protective effect of labral reconstruction in a porcine model. Methods Twelve pigs (24 hips) were divided into 3 groups: labrum defect group, lateral meniscus (LM) allograft group, and LM allograft wrapped with acellular peritoneum matrix (LM-APM) group before undergoing bilateral hip surgery. The pigs were sacrificed at 12 and 24 weeks postoperatively, while the femoral head cartilage was retrieved and then subjected to imaging measurement, macrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The current study successfully established labral reconstruction with a meniscus allograft in a pig model. Animal model studies have reported on labral reconstruction with tendons [29,31] and have provided evidence supporting its ability to maintain the integrity of the articular cartilage [31,36]. Nonetheless, none of these studies conducted a biomechanical analysis of the tendon graft.…”
Section: Discussion Of Key Findingsmentioning
confidence: 99%
“…The current study successfully established labral reconstruction with a meniscus allograft in a pig model. Animal model studies have reported on labral reconstruction with tendons [29,31] and have provided evidence supporting its ability to maintain the integrity of the articular cartilage [31,36]. Nonetheless, none of these studies conducted a biomechanical analysis of the tendon graft.…”
Section: Discussion Of Key Findingsmentioning
confidence: 99%
“…This clinical study [16] has the longest follow-up of segmental acetabular labral reconstruction techniques; the authors demonstrated 60% survivorship at 10 years with revision hip arthroscopy or hip arthroplasty as the outcome, with 87% of patients obtaining a patient-acceptable symptom state on the Hip Outcome Score-activities of daily living scale at the final follow-up.An in vivo study in pigs found that segmental labral reconstruction with lateral meniscus allograft improved Osteoarthritis Research Society International scores in the femoral head cartilage in the region of the defect relative to a labral defect, suggesting there are chondroprotective effects of labral reconstruction with this technique [21]. A comparative, retrospective clinical study evaluated circumferential labral reconstruction versus labral repair at a minimum of 5 years and determined that both groups of patients had similar improvements in patient-reported outcomes and need for further reoperations (revision hip arthroscopy or THA), even though patients in the labral reconstruction cohort were older and had more severe chondrolabral damage [17].…”
Section: Read This Nextmentioning
confidence: 99%
“…An in vivo study in pigs found that segmental labral reconstruction with lateral meniscus allograft improved Osteoarthritis Research Society International scores in the femoral head cartilage in the region of the defect relative to a labral defect, suggesting there are chondroprotective effects of labral reconstruction with this technique [21].…”
Section: Read This Nextmentioning
confidence: 99%